Infection and inflammation impacts on oncogenesis - Dittmar, Thomas 1966-; Zänker, Kurt S. 1946-; Schmidt, Axel 1962- (Contributions to microbiology, 2006)
The last two decades have shown that the local microenvironment plays a pivotal role in cancer progression. Cancer is not the result of mutation events in single cells, but of a complex interplay of tumor cells, inflammatory cells, stem cells, growth factors, cytokines, chemokines and DNA-damaging agents.This book provides an up-to-date overview of how infections and chronic inflammatory conditions can give rise to the onset of a malignant phenotype, a theory that was originally postulated by Rudolf Virchow as early as 1863. Internationally recognized experts discuss novel aspects such as the role of stem cells and the occurrence of aneuploidy in carcinogenesis. Several examples of pathogens and their correlation with specific cancer types are described, e.g. Helicobacter pylori and gastric neoplasia, and schistosomiasis and bladder cancer. The mechanisms of carcinogenesis are examined in detail as are the types of cells that can transform to a malignant phenotype, with special emphasis on stem cells which have recently been shown to give rise to cancer. Further chapters discuss the role of chemokines in directing metastasis and describe options for visualizing metastasis formation in 3-dimensional model systems and in the living body.Our increasing knowledge of the inflammatory microenvironment’s role in the carcinogenic process will be the basis for investigating new anti-inflammatory strategies to counter tumor formation and growth. Therefore, this book is essential reading for scientists and clinicians working in cancer research and prevention